2019
DOI: 10.1103/physreva.100.023802
|View full text |Cite
|
Sign up to set email alerts
|

Photon statistics of a quantum emitter close to a lattice of plasmonic nanoparticles

Abstract: We study theoretically the statistics of photons generated by a quantum emitter located in the vicinity of a periodic plasmonic nanostructure. The presented formalism is based on a macroscopic QED formalism in conjunction with a density-matrix approach in order to obtain the second-order correlation function of the emitted photons accounting for the influence of the plasmonic environment. The metallic reservoir coupling is computed using Green's-function theory, which, for a periodic lattice of scatterers, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Figure 2 shows, for photon energy 1.517 eV, the tangential and radial enhancement factors |E x | and |E z | of the electric fields, respectively, as well as the enhancement factor for the decay rate of the quantum emitter [31]. The results presented in figure 2 are in agreement with that presented in references [32][33][34]. We observe that the |E x | factor decreases up to d ≈ 5 nm, but after that point, it starts to increase; however at all d shown here, its value is smaller than one.…”
Section: Theorysupporting
confidence: 85%
“…Figure 2 shows, for photon energy 1.517 eV, the tangential and radial enhancement factors |E x | and |E z | of the electric fields, respectively, as well as the enhancement factor for the decay rate of the quantum emitter [31]. The results presented in figure 2 are in agreement with that presented in references [32][33][34]. We observe that the |E x | factor decreases up to d ≈ 5 nm, but after that point, it starts to increase; however at all d shown here, its value is smaller than one.…”
Section: Theorysupporting
confidence: 85%
“…In [ 131 ], the authors showed that the presence of a plasmonic NP leads as to a strong modification of the resonance fluorescence spectrum, as to transition from antibunching to bunching for fluorescent photons. In [ 144 ], the same authors investigated the statistics of the emission of a two-level QE near the same two-dimensional array of dielectric nanospheres with a metal coating. It was shown that the photon statistics is significantly modified by a lattice of NPs.…”
Section: Quantum Optics Of a Qe In The Near Field Of An Npmentioning
confidence: 99%
“…However, there is another widely used methodology for studying light-matter interaction in quantum systems near plasmonic nanostrucrures which is based on the electromagnetic Green's tensor, see, e.g., Refs. [63][64][65][66][67][68] , which uses linear density matrix equations, as the Green's tensor does not lead to a direct nonlinearity in the density matrix equations. One may induce indirectly a nonlinearity in the linear density matrix equations of the electromagnetic Green's tensor approach when a self-consistent scheme is considered and the local field correction to the electric field interacting with the quantum system is introduced, as it was shown by Hayati et al 69 .…”
Section: Theory Of the Hybrid Nanostructurementioning
confidence: 99%